Monitoring disease progression in childhood bronchiectasis - Ramsey, Kathryn A.; Schultz, André (Frontiers in Pediatrics, 2022)
Bronchiectasis (not related to cystic fibrosis) is a chronic lung disease characterised by abnormal airway dilatation that impairs quality of life and reduces life expectancy. Patients experience chronic wet cough and recurrent pulmonary exacerbations often requiring hospitalisation. Early diagnosis and management of childhood bronchiectasis is essential to prevent respiratory decline, optimise quality of life, minimise pulmonary exacerbations, and potentially reverse bronchial disease. Disease monitoring potentially allows for 1) the early detection of acute exacerbations, thereby facilitating timely intervention, 2) tracking the rate of disease progression for prognostic purposes, and 3) quantifying the response to therapies. This review article will discuss methods for monitoring disease progression in children with bronchiectasis, including lung imaging, respiratory function, patient reported outcomes, respiratory exacerbations, sputum biomarkers, and nutritional outcomes.